Carbon nanotubes: A potential concept for drug delivery applications - Kumar R.; Dhanawat M.; Kumar S.; Singh B.N.; Pandit J.K.; Sinha V.R. (My University, 2025)
The unique properties of carbon nanotubes (CNTs) make them a highly interesting and demandable nanocarrier in the field of nanoscience. CNTs facilitate efficient delivery of therapeutics like drugs, proteins, genes, nucleic acids, vitamins and lot more. Even though highly beneficial, the biocompatibility of CNTs is a major issue in their questioning their potential application in targeting drug delivery. Studies confirmed subdued toxicity of CNTs following slight modifications like functionalization, controlled dimensions, purification etc. A well-established mechanism for cellular internalization is an insistent need to attain a more efficient and targeted delivery. Recent patents have been thoroughly discussed in the text below. © 2014 Bentham Science Publishers.